Effect of Cross‐Link Density on Carbon Dioxide Separation in Polydimethylsiloxane‐Norbornene Membranes. Issue 21 (20th October 2015) - Hong, Tao; Niu, Zhenbin; Hu, Xunxiang; Gmernicki, Kevin; Cheng, Shiwang; Fan, Fei; Johnson, J. Casey; Hong, Eunice; Mahurin, Shannon; Jiang, De‐en; Long, Brian; Mays, Jimmy; et al.
Abstract: The development of high‐performance materials for carbon dioxide separation and capture will significantly contribute to a solution for climate change. Herein, (bicycloheptenyl)ethyl‐terminated polydimethylsiloxane (PDMSPNB) membranes with varied cross‐link densities were synthesized via ring‐opening metathesis polymerization. The developed polymer membranes show higher permeability and better selectivity than those of conventional cross‐linked PDMS membrane. The achieved performance (CO2 permeability≈6800 Barrer; CO2 /N2 selectivity≈14) is very promising for practical applications. The key to achieving this high performance is the use of an in situ cross‐linking method for difunctional PDMS macromonomers, which provides lightly cross‐linked membranes. By combining positron annihilation lifetime spectroscopy, broadband dielectric spectroscopy, and gas solubility measurements, key parameters necessary for achieving excellent performance have been elucidated. Abstract : Let CO2 pass ! The influence of the variation of cross‐link density in end‐group cross‐linked polydimethylsiloxane‐norbornene (PDMSPNB) matrix on CO2 permeability and CO2 /N2 selectivity is investigated. Tuning cross‐link densities of PDMS membranes using macromonomers can improve CO2 /N2 separation significantly. The cross‐linked PDMSPNB membranes give rise to excellent CO2 permeability with good selectivity.